Seroprevalence of antibodies to enterovirus 71 and coxsackievirus A16 among people of various age groups in a northeast province of Thailand - Lerdsamran, Hatairat; Prasertsopon, Jarunee; Mungaomklang, Anek; Klinmalai, Chompunuch; Noisumdaeng, Pirom; Sangsiriwut, Kantima; Tassaneetrithep, Boonrat; Guntapong, Ratigorn; Iamsirithaworn, Sopon; Puthavathana, Pilaipan (Virology journal, 2018)
Hand, foot and mouth disease (HFMD) is endemic among population of young children in Thailand. The disease is mostly caused by enterovirus 71 (EV71) and coxsackievirus A16 (CA16). This study conducted serosurveillance for neutralizing (NT) antibodies to EV71 subgenotypes B5 and C4a, and to CA16 subgenotypes B1a and B1b, in 579 subjects of various ages using a microneutralization assay in human rhabdomyosarcoma (RD) cells. These test viruses were the major circulating subgenotypes associated with HFMD in Thailand during the study period. We found that the levels of seropositivity against all 4 study viruses were lowest in the age group of 6-11 months, i.e., 5.5% had antibody to both EV71 subgenotypes, while 14.5% and 16.4% had antibody to CA16 subgenotypes B1a and B1b, respectively. The percentages of subjects with antibodies to these 4 viruses gradually increased with age, but were still less than 50% in children younger than 3 years. These laboratory data were consistent with the epidemiological data collected by the Ministry of Public Health which showed repeatedly that the highest number of HFMD cases was in children aged 1 year. Analyses of amino acid sequences of the test viruses showed 97% identity between the two subgenotypes of EV71, and 99% between the two subgenotypes of CA16. Nevertheless, the levels of seropositivity and antibody titer against the two subgenotypes of EV71 and of CA16 were not significantly different. This study clearly demonstrated NT antibody activity across EV71-B5 and EV71-C4a subgenotypes, and also across CA16-B1a and CA16-B1b subgenotypes. Moreover, there were no significant differences by gender in the seropositive rates and antibody levels to any of the 4 virus subgenotypes.